1991
DOI: 10.1530/acta.0.1250109
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin influences preovulatory follicular development and advances ovulation in rats

Abstract: Oxytocin has been shown to advance gonadotropin secretion in pro-estrus rats. The effects that oxytocin-induced changes have on the ovary were investigated in this study. Oxytocin administered to rats at proestrus 09.00 h, 10.00 h and 11.00 h advanced follicular growth, progesterone secretion, and the time of ovulation. However, both treated and control groups of rats ovulated similar numbers of oocytes and the oocytes released were of similar fertility. Because oxytocin has been shown to induce early LH and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Early work on the rabbit found that treatment with oxytocin or oxytocin antiserum shortly before mating or hCG treatment blocked ovulation (Brinkley & Nalbandov, 1963;Roca et ., 1978). Robinson et al (1985) found that administration of oxytocin to cyclic mice in early pro-oestrus induced more preantral follicles and an earlier ovulation than in control mice, and similar exper¬ iments in rats advanced the time of ovulation by about 3 h (Robinson & Evans, 1991). However, all oxytocin-treated ewes in the present experiment ovulated, and the histological appearance of the corpus luteum approximately one day after ovulation did not differ following treatment.…”
Section: Discussionsupporting
confidence: 62%
“…Early work on the rabbit found that treatment with oxytocin or oxytocin antiserum shortly before mating or hCG treatment blocked ovulation (Brinkley & Nalbandov, 1963;Roca et ., 1978). Robinson et al (1985) found that administration of oxytocin to cyclic mice in early pro-oestrus induced more preantral follicles and an earlier ovulation than in control mice, and similar exper¬ iments in rats advanced the time of ovulation by about 3 h (Robinson & Evans, 1991). However, all oxytocin-treated ewes in the present experiment ovulated, and the histological appearance of the corpus luteum approximately one day after ovulation did not differ following treatment.…”
Section: Discussionsupporting
confidence: 62%
“…Female mice lacking OXT are fertile and able to deliver pups [ 35 ]. Administration of OXT has no effects on the number of follicles and the ovulation rate [ 36 , 37 ], but the abundance of Oxtr mRNA in GCs suggests a role of OXT in follicular development. OXT has been shown to stimulate the production of LH in the pituitary [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…(Wathes et al 1992). rather than with direct effects on the process of or.ulation as observed in the rat (Evans et al 1989;Robinson and Evans 1991). It is possible that the quantify of OT was not sufficient to elicit the expected response.…”
Section: Time Of Ovulationmentioning
confidence: 97%